2013
DOI: 10.1111/1574-6941.12173
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of IncP-1 plasmids and IS1071insertion sequences in on-farm biopurification systems and other pesticide-polluted environments

Abstract: Mobile genetic elements (MGEs) are considered as key players in the adaptation of bacteria to degrade organic xenobiotic recalcitrant compounds such as pesticides. We examined the prevalence and abundance of IncP-1 plasmids and IS1071, two MGEs that are frequently linked with organic xenobiotic degradation, in laboratory and field ecosystems with and without pesticide pollution history. The ecosystems included on-farm biopurification systems (BPS) processing pesticide-contaminated wastewater and soil. Comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
43
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 53 publications
(78 reference statements)
7
43
0
Order By: Relevance
“…The very high relative abundances of the promiscuous IncP-1 plasmids detected in the BPS are comparable to those seen with other "hot spots" of horizontal gene transfer such as manure, sewage, or polluted river sediments (39,40). Our data confirm the results of two recent studies using TC-DNA from different BPS which also found an unusually high abundance of IncP-1 plasmids in the BPS (15,37). Interestingly, the abundance of IncP-1 plasmids seemed to be increased in BPS bacteria, likely in response to the exposure to different types and concentrations of pesticides as recently reported by Jechalke et al (14).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The very high relative abundances of the promiscuous IncP-1 plasmids detected in the BPS are comparable to those seen with other "hot spots" of horizontal gene transfer such as manure, sewage, or polluted river sediments (39,40). Our data confirm the results of two recent studies using TC-DNA from different BPS which also found an unusually high abundance of IncP-1 plasmids in the BPS (15,37). Interestingly, the abundance of IncP-1 plasmids seemed to be increased in BPS bacteria, likely in response to the exposure to different types and concentrations of pesticides as recently reported by Jechalke et al (14).…”
Section: Discussionsupporting
confidence: 89%
“…In accordance with previous findings (14,37), we hypothesize that temporal changes in the abundance and diversity of MGEs in an on-farm BPS might be caused by changes in the composition and concentration of the pesticides added to the BPS over the course of the agricultural season. To test our hypothesis and to provide the first more comprehensive view on the mobilome of BPS bacterial communities, cultivation-independent techniques were applied to investigate shifts in the abundance and diversity of the MGEs of bacterial communities of a BPS in operation on a farm in Kortrijk, Belgium, over the course of the agricultural season of 2011.…”
supporting
confidence: 91%
See 3 more Smart Citations